The Hackable City Digital Media and Collaborative City-Making in the Network Society - de Lange, Michiel; de Waal, Martijn (Springer Nature Singapore : Imprint: Springer, 2019)
This open access book presents a selection of the best contributions to the Digital Cities 9 Workshop held in Limerick in 2015, combining a number of the latest academic insights into new collaborative modes of city making that are firmly rooted in empirical findings about the actual practices of citizens, designers and policy makers. It explores the affordances of new media technologies for empowering citizens in the process of city making, relating examples of bottom-up or participatory practices to reflections about the changing roles of professional practitioners in the processes, as well as issues of governance and institutional policymaking.